Polybrominated diphenyl ethers in serum from residents living in a brominated flame retardant production area: Occurrence, influencing factors, and relationships with thyroid and liver function. (1st February 2021) - Zhao, Xuezhen; Yang, Xiaodi; Du, Yinglin; Li, Renbo; Zhou, Tao; Wang, Yuwei; Chen, Tian; Wang, Dejun; Shi, Zhixiong
Abstract: Polybrominated diphenyl ethers (PBDEs) have been used as flame retardants (FRs) in China for decades, even after they were identified as persistent organic pollutants. In this study, serum samples were collected from 172 adults without occupational exposure who were residents of a well-known FR production region (Laizhou Bay, north China), and PBDE congeners were measured to assess their occurrence, congener profile and influencing factors in serum. Moreover, the relationships between serum concentrations of PBDEs and thyroid/liver function indicators were analyzed to evaluate whether human exposure to PBDEs would lead to thyroid/liver injury. All 8 PBDE congeners were detected at higher frequencies and serum concentrations than those found in general populations. The median levels of ∑PBDEs, BDE-209 and ∑3-7 PBDEs (sum of tri-to hepta-BDEs) were 64.5, 56.9 and 7.2 ng/g lw (lipid weight), respectively, which indicated that deca-BDE was the primarily produced PBDE in Laizhou Bay and that the lower brominated BDEs were still ubiquitous in the environment. Gender was a primary influencing factor for some BDE congeners in serum; their levels in female serum samples were significantly lower than those in male serum samples. Serum PBDE levels showed a downward trend with increased body mass index (BMI), which might reflect the increasing serum lipid contents. Serum levels of some BDE congeners were significantly positively correlated with certain thyroid hormones and antibodies, including free triiodothyronine (fT3), total triiodothyronine (tT3), total thyroxine (tT4) and thyroid peroxidase antibody (TPO-Ab). Levels of some congeners were significantly negatively correlated with some types of serum lipid, including cholesterol (CHOL), low density lipoprotein (LDL) and total triglyceride (TG). Other than serum lipids, only two liver function indicators, total protein (TP) and direct bilirubin (DBIL), were significantly correlated with certain BDE congeners (BDE-100 and BDE-154). Our results provide new evidence on the thyroid-disrupting and hepatotoxic effects of PBDEs. Graphical abstract: Image 1 Highlights: PBDEs were determined in serum collected from residents of a BFR production region. All PBDE congeners presented high detection frequencies and serum concentrations. Gender and BMI were main influencing factors on serum PBDE concentrations. BDE-47, BDE-99 and BDE-100 might disturb thyroid homeostasis in human being. Serum BDE-100 and -154 were significantly correlated with some liver biomarkers. Abstract : Main finding: High levels of PBDEs were found in serum samples from residents of a brominated flame retardant production region and were significantly correlated with thyroid/liver injury.